LEGAL ANALYSIS OF THE POSITION OF SOCIAL RESEARCH REPORT ON CHILD CRIMINAL DECISIONS - Tambunan, Samuel Parsaoran (NOMOI Law Review, 2024)
Criminal sanctions are The Last Resort or ultimum remedy which is applied after other developmental and preventive efforts have failed. In the juvenile criminal case number. 14/Pid.Sus-Anak/2018/PN.Mdn and Decision Number. 48/Pid.Sus-Anak/2019/PN.Mdn, Children were sentenced to prison for theft even though recommendations from Community Guidance Officers prioritized children's growth and development. This research analyzes the role of Community Development Officers in the Juvenile Criminal Justice System, what the Community Development Officer conveys to the Judge to be taken into consideration in the Decision, and the position of the Community Research Report in the Judge's consideration in Decision Number. 14/Pid.Sus-Anak/2018/PN.Mdn and Decision Number. 48/Pid.Sus-Anak/2019/PN.Mdn. The research method used in this research is normative juridical with a statutory approach and case studies. The research results show that in decision number. 14/Pid.Sus-Anak/2018/PN.Mdn and Decision Number. 48/Pid.Sus-Anak/2019/PN.Mdn, the position of the Community Research Report is only a reference. The judge did not even consider that in this case there had been a peaceful settlement between the victim witness and the child. When examining and deciding cases, judges should consider the Public Research Report in depth.